Regulatory Institutions and Instruments and Their Position in Rail Transportation Industry; Lessons for Iran - Mohammad Azimzadeh Arani; Farshad Momeni (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2017)
Today, because of market failure in market–based economies, government regulation through regulatory bodies is vital. Rail transportation industry like other network industries has faced market failure because of its properties such as natural monopoly, nature of its multi-product activity, the specific role of rail infrastructure and externalities. Thus, this industry needs to be monitored by the regulatory bodies. This article is prepared by analytical-descriptive method in two parts. In the first part, principles, nature and instruments of regulation are examined and their position in rail transportation industry, especially in Iran, is addressed in the second part. The results show that the regulatory instruments are divided into competition laws and sectoral regulation which are related to competitive and noncompetitive markets respectively and they have separate function to each other. In Rail transportation industry, the infrastructure sector due to its natural monopoly is noncompetitive and the operating sector is competitive. In Iran, although significant steps have been taken to separate competitive and noncompetitive sectors as a law of free access to the rail network was passed but The Railways of I.R.I Company as the regulator of this industry is faced with serious challenges such as lack of independence, lack of appropriate mechanism for accountability and overlapping functions with other governmental bodies.